The operational evidence base for delivering direct nutrition interventions to improve child nutrition and health in India: A review - Partnerships and Opportunities to Strengthen and Harmonize Actions for Nutrition in India (International Food Policy Research Institute, 2013)
The persistence of undernutrition in the face of India’s impressive economic growth continues to be of enormous concern. Less than 55% of mothers and children receive any of the essential health and nutrition inputs. POSHAN conducted a desk review to understand how evidence-based direct nutrition interventions are reflected in program design and how they are operationalized within the program landscape for improving maternal and child nutrition in India.